Genome sequence of Shinella sp. strain DD12, isolated from homogenized guts of starved Daphnia magna - Poehlein, Anja (Stand Genomic Sci, 2016)
Shinella sp. strain DD12, a novel phosphite assimilating bacterium, has been isolated from homogenized guts of 4 days starved zooplankton Daphnia magna. Here we report the draft genome of this bacterium, which comprises 7,677,812 bp and 7505 predicted protein-coding genes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40793-015-0129-3) contains supplementary material, which is available to authorized users.